Analisis Perilaku Kecurangan Akademik Siswa dalam Pelaksanaan Ujian di Sekolah - Zayyinul Mushthofa; Ani Rusilowati; Sulhadi Sulhadi; Putut Marwoto; Budi Naini Mindiyarto (Universitas Pendidikan Mandalika (UNDIKMA), 2021)
This study aims to describe the popular types of academic dishonesty, teachers' supervision, and the factors which motivate students to cheat. This research used the descriptive quantitative method with 260 students as respondents from 4 schools. Questionnaires were given online to the students. The data analysis technique used statistic descriptive. The result showed that the popular types of academic dishonesty among the students were asking their friends, carrying small notes, searching the answer on the web via cell phones, carrying textbooks, and etcetera. The teachers’ or supervisors’ supervision was good, but there were times when they were careless so that the students used the opportunity to cheat. During online examination supervision, the students stated that there was no particular supervision; therefore they took the advantage of this opportunity. The driving factors which caused the students to cheat were they considered the questions were too difficult; they did not have confidence in their own answers or abilities; they did not study; they had an opportunity to cheat; they wanted good grades, and they had some unanswered questions but the time was almost over.